Excess conductivity of Cu0.5Tl0.5Ba2Ca3Cu4–yZnyO12–δ - Khan, Nawazish A.; Hasnain, S.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Oxide high-Tc superconductors (HTSC) are anisotropic in character since the charge carriers have free momentin the conducting CuO2 planes [1] whereas their motion is impeded by insulating/partially insulating MBa2O4–δ (M = Y, Bi, Hg, Tl, CuTl, etc.) charge reservoir layers. In the transport process the charge carriers have to tunnel across insulating/partially insulating barriers along the c-axis and across the grain boundaries,which promote a fluctuation in the order parameter and in turn to the conductivity of the carriers. The studies of such fluctuation conductivity (FIC) may help in understanding the intrinsic mechanism of superconductivity. Here the electrical resistivity ρ(T) versus temperature data of as-prepared and oxygen post-annealedCu0.5Tl0.5Ba2Ca3Cu4–yZnyO12–δ (y = 0, 0.5, 1.5, 2.5) samples is studied for FIC analyses in the temperature regimewell above the critical temperature; such analyses have been carried out by employing Lawrence and Doniach (LD) and Maki–Thompson (MT) models. The coherence length, inter-plane coupling, exponent, dimensionality of fluctuations and the phase relaxation time of the carriers are determined from such analyses. It is observed that the crossover temperature associated with two distinct exponents fits very well with the two-dimensional (2D) and three-dimensional (3D) LD equations. The crossover temperature T0 is shifted to higher temperatures with enhanced Zn doping. The 3D LD region is shifted to higher temperature with the increased Zn doping. We have elucidated from these analyses that lower Tl content in the final compound may increase the charge carrier’s doping efficiency of MBa2O4–δ charge reservoir layer, resulting into an increase in the coherence lengthalong the c-axis and superconductivity parameters. A small decrease in the coherence length along the c-axis ξc(0) is observed in the samples with Zn doping of y = 1.5 whereas ξc(0) increases in the samples y = 0.5, 2.5. Incomparison with as-prepared samples, the ξc(0) decreases after post-annealing in oxygen atmosphere. It is most likely that a decrease in the density of charge carrier’s is promoted by oxygen diffusion in the unit cell may suppressthe ξc(0). The increase oxygen diffusion is evidenced from the softening of phonon modes after postannealing in oxygen atmosphere. The decreased population of small spins of Cu atoms induced by doping of Zn is viewed in the terms of suppression of spin gap and hence the pseudo-gap in Cu0.5Tl0.5Ba2Ca3Cu4–yZnyO12–δ (y = 0, 0.5, 1.5, 2.5) samples.